Incivility in nursing education: a case study in Indonesia - Eka, Ni Gusti Ayu (2017)
Background: Many problems of incivility/uncivil behaviour have been faced by nursing education globally from disrespectful to violent behaviour. However, most research on this subject has been carried out in Western countries with regard to psychological viewpoints (e.g. physical and emotional disadvantages). Indonesia is an excellent case study as a developing country with over 700 ethnicities and diverse socio-economic backgrounds and six official religions; these conditions can shape behaviours in nursing education.